RISK-ORIENTED PREDICTION OF PREGNANCY LOSS PATHOLOGY BASED ON A PERSONALIZED APPROACH - Nataliia Timchenko; Taras Gutor (Acta Medica Leopoliensia)
The increase in the frequency of pregnancy loss and the negative prognostic trend with the probable development of the demographic crisis in connection with the martial law in Ukraine and the mass migration of the female population provoked by it, requires the search for all possible ways of prevention and prophylactic of this pathology.